Example-based dynamic deformation - Zhang, Wenjing (2016)
This research investigates computational models and algorithms for efficiently incorporating example-based techniques into traditional physically-based deformable models to generate example-based dynamic deformation. Simulating deformable model plays a very important role in computer graphics and animation. While physically-based deformation provides highly realistic effects, it faces difficulties in high-level artistic deformation required in certain areas like computer animations. On the other hand, example-based techniques provide intuitive control for the deformation results by designing examples, which easily represent the high-level intention about the desired deformation. However, most of the existing example-based techniques focus on static deformation and interesting dynamics can be hardly captured. Thus, it is tempting to combine physically-based deformation techniques and example-based techniques for modelling dynamic deformation. Previous attempts addressing the problem either suffer from computational burden or sacrifice physical plausibility. The objectives of our research are thus to develop new computational models and algorithms that provide the user intuitive example-based approaches to control physically-based deformation, reduce the computation complexity and meanwhile preserve the physical plausibility as much as possible.